Minat Generasi Muda Buddhis Untuk Menjadi Penyuluh Agama Buddha Di Kabupaten Wonogiri - Putra, Mirayadi Anto; Tantra, Manggala Wiriya (Universitas Islam Negeri Raden Intan Lampung, 2024)
The focus of this article is to conduct research on the interest of young Buddhists to become Buddhist religious educators. This research utilizes descriptive qualitative method. Data were collected through observation, interviews and documentation. The subject of this research is the Buddhist Young Generation in Wonogiri Regency. Data validity was tested using data triangulation. To obtain valid data, researchers analyzed the data by data reduction, data presentation and drawing conclusions. From the results of the study, it was found that young Buddhists have a low interest in becoming Buddhist religious instructors. This condition is caused by several factors, namely internal and external. Internal factors consist of the young generation's lack of knowledge about Buddhist religious instructors, the young generation's self-confidence and interest in religious instructors' activities. While external factors consist of environment, family, education and the involvement of young Buddhists.